Vulnerability to Freshwater Changes in the Inuit Settlement Region of Nunatsiavut, Labrador: A Case Study from Rigolet - Goldhar, Christina; Bell, Trevor; Wolf, Johanna (ARCTIC, 2014)
Drawing on vulnerability approaches from the climate change literature, this paper explores the vulnerability of residents of the community of Rigolet, Nunatsiavut, Labrador, to changes in freshwater. Our approach emphasizes local preferences and values. We analyze the results from 89 household interviews (88% response) and targeted interviews in Rigolet to consider the human experience of climate variability and change. Residents report that changes in the spatial and temporal distribution of freshwater are currently challenging their ability to access preferred drinking water and food sources and are adding to the financial barriers that restrict their time spent on the land. The results of our study suggest that Rigolet residents are successfully adapting to existing freshwater changes in their watershed, though these adaptations have not come without sacrifice. The adaptive capacity of Rigolet residents has been supported by resource flexibility and experience-based knowledge of freshwater variability within their watershed, among other factors. Findings suggest that the exposure of sub-Arctic and Arctic communities to freshwater changes and their capacity to adapt are largely shaped by the lifeways of residents and the manner and degree to which they are dependent on local freshwater systems. Cet article explore la vulnérabilité des résidents de Rigolet, au Nunatsiavut, Labrador, vis-à-vis des changements caractérisant l’eau douce en s’appuyant sur les approches de vulnérabilité puisées dans la documentation sur le changement climatique. Notre démarche met l’accent sur les préférences et les valeurs locales. Nous analysons les résultats de 89 entrevues réalisées auprès de divers ménages (taux de réponse de 88 %) et d’entrevues ciblées effectuées à Rigolet afin de considérer la réaction de l’être humain vis-à-vis de la variabilité et du changement climatique. Les résidents signalent que les changements enregistrés sur le plan de la répartition spatiale et temporelle de l’eau douce leur posent des ...